The imperfection-sensitivity of origami crash boxes. (February 2017) - Wang, Bo; Zhou, Caihua
Abstract: A novel thin-walled tube, named as origami crash box, is recognized as a promising energy absorption device. Experimental results reveal that unintentional imperfection could trigger the symmetric mode with low mean crushing force rather than a high-performance mode, known as complete diamond mode. Therefore, the imperfection-sensitivity of origami crash boxes is investigated in this paper. Appropriate geometric imperfection which is regarded as a substitution of the real defect is introduced into finite element models to trigger the symmetric mode. Numerical simulation shows that the specific energy absorption SEA declines with the increase in imperfection amplitude A i . And a critical value of ratio A i / t t hat is just able to trigger the symmetric mode is obtained. A detailed parametric analysis indicates that a suitable geometry is beneficial to improve the compliance of origami crash box, leading to stable collapse behavior with higher performance in terms of energy absorption. Moreover, a bulkhead reinforced origami crash box is proposed as a low imperfection-sensitivity energy absorption device. And an optimal wall thickness ratio t 1 /t is obtained through numerical analysis. Highlights: Appropriate geometric imperfection could successfully trigger the symmetric mode. SEA declines with the increase in imperfection amplitude. Lower dihedral angle ϑ and higher ratio b/t improve the compliance of origami crash box. A bulkhead reinforced tube is proposed as an imperfection insensitivity structure.